2004
DOI: 10.1001/archinte.164.20.2206
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Infection

Abstract: The clinical implications of our findings include emphasizing the importance of smoking cessation as part of the therapeutic plan for people with serious infectious diseases or periodontitis, and individuals who have positive results of tuberculin skin tests. Controlling exposure to secondhand cigarette smoke in children is important to reduce the risks of meningococcal disease and otitis media, and in adults to reduce the risk of influenza and meningococcal disease. Other recommendations include pneumococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
663
5
25

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 868 publications
(749 citation statements)
references
References 116 publications
(124 reference statements)
20
663
5
25
Order By: Relevance
“…The high rate of catheter use in the initial blood access might also contribute to the higher risk of bacteremia in patients with a shorter duration of hemodialysis. Smokers may have increased susceptibility to infection due to alterations in the respiratory tract and decreased immune response (14). Previous research also indicated that smoking was a risk factor for bacteremia-related hospitalization and mortality (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of catheter use in the initial blood access might also contribute to the higher risk of bacteremia in patients with a shorter duration of hemodialysis. Smokers may have increased susceptibility to infection due to alterations in the respiratory tract and decreased immune response (14). Previous research also indicated that smoking was a risk factor for bacteremia-related hospitalization and mortality (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…From a non‐exhaustive review of the literature, we identified potential confounders: insurance coverage, 12 , 13 number of primary care physicians per 100 000 population, 14 , 15 environmental humidity, 11 , 16 chronic disease and pregnancy rates, 17 , 18 , 19 , 20 percentage of the county population living below the poverty level, 12 , 21 , 22 vaccination uptake, 23 , 24 , 25 racial composition, 26 , 27 , 28 , 29 population density, 30 , 31 and prevalence of smoking 32 , 33 , 34 . A concise description of data sources and variable definitions for all covariates is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Cigarette smoking is well recognized to increase the susceptibility to bacterial and viral infections ( Arcavi & Benowitz, 2004 ). Exposure to cigarette smoking damages the lining of the respiratory tract, reduces mucociliary clearance, and impairs both humoral and cellular immune responses ( Dye & Adler, 1994 ).…”
Section: Discussionmentioning
confidence: 99%